2020
DOI: 10.22238/rc2448269220201801107128
|View full text |Cite
|
Sign up to set email alerts
|

Análise De Impactos Ambientais Em Área De Preservação Permanente (App) Como Instrumento De Gestão Em Rios Urbanos

Abstract: As Áreas de Preservação Permanente (APP) são áreas nas quais a vegetação deve ser mantida, a fim de se garantir a preservação dos recursos hídricos, a estabilidade geológica, a biodiversidade, e consequentemente o bem-estar humano. No entanto, quando localizadas ao entorno dos cursos hídricos, sobretudo em centros urbanos, as APP têm sido transformadas e ocupadas, gerando prejuízos ambientais e sociais. Diante do exposto, o objetivo deste trabalho foi avaliar os impactos ambientais sobre os aspectos ág… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The Ribeirão Anhumas Permanent Protection Area study in Campinas found that, in an area of urban influence, the LAI value varied between 1.311 m 2 /m 2 (dry) and 1.398 m 2 /m 2 (rain) and in a predominantly rural area, it varied between 1.548 m 2 /m 2 (dry) and 1.826 m 2 /m 2 (rain). Such values correlate with the values of organic matter and CEC of the soil so the lowest values for these indicators were obtained for the point located in an urban area and the highest values were obtained for the area of rural approximation [47].…”
Section: Spatial Variation Of Soil Properties and Vegetation Covermentioning
confidence: 87%
“…The Ribeirão Anhumas Permanent Protection Area study in Campinas found that, in an area of urban influence, the LAI value varied between 1.311 m 2 /m 2 (dry) and 1.398 m 2 /m 2 (rain) and in a predominantly rural area, it varied between 1.548 m 2 /m 2 (dry) and 1.826 m 2 /m 2 (rain). Such values correlate with the values of organic matter and CEC of the soil so the lowest values for these indicators were obtained for the point located in an urban area and the highest values were obtained for the area of rural approximation [47].…”
Section: Spatial Variation Of Soil Properties and Vegetation Covermentioning
confidence: 87%